PENGARUH STRATEGI HARGA DAN PROMOSI TERHADAP MINAT BELI KONSUMEN DI SUPERMARKET YOGYAKARTA - Leki, Nafsir; Zuraida, Lukia (Yudishtira Journal : Indonesian Journal of Finance and Strategy Inside, 2025)
Purpose: This study aims to analyze the effect of pricing strategy and sales promotion on consumer purchase intention in supermarkets in Yogyakarta using the SEM-PLS approach. SEM-PLS is chosen due to its ability to handle complex models with multiple latent variables, even with small sample sizes and non-normally distributed data.  Methodology/approach: The research was conducted in supermarkets in Yogyakarta using a quantitative approach. Data were collected through a questionnaire with a Likert scale of 1-5 and analyzed using the SmartPLS software. The study involved testing the measurement model (validity and reliability) and the structural model (path coefficients, R², bootstrapping significance, effect size, and predictive relevance).  Results/findings: The findings indicate that both pricing strategy and sales promotion have a significant positive effect on consumer purchase intention. The model demonstrates good predictive relevance, suggesting that pricing and promotional strategies are crucial factors influencing consumer behavior in supermarkets. However, this study is limited to a specific supermarket setting in Yogyakarta, and the results may not be generalizable to other retail contexts or regions.  Limitations: This study is limited to a specific supermarket setting in Yogyakarta, and the results may not be generalizable to other retail contexts or regions. The relatively small sample size may also affect the robustness of the findings. Contribution: This research contributes to the field of marketing, particularly in retail and consumer behavior studies. The findings provide valuable insights for supermarket managers and marketing strategists in optimizing pricing and promotional strategies to enhance consumer purchase intention